An exploratory study on the checkout rate of circulating tumor cells and the prediction of efficacy of neoadjuvant therapy and prognosis in patients with HER-2-positive early breast cancer - Zhou, Jinmei; Wu, Jiangling; Hao, Xiaopeng; Li, Ping; Zhang, Huiqiang; Wu, Xuexue; Chen, Jiaxin; Liu, Jiawei; Xiao, Jinyi; Zhang, Shaohua; Jiang, Zefei; Yang, Yanlian; et al. (Frontiers in Oncology, 2022)
Background: Neoadjuvant therapy is a standard treatment for patients with large, nonmetastatic breast cancer and may allow breast-conserving surgery after tumor downsizing while decreasing the risk of subsequent relapse. Dynamic changes of circulation tumor cells (CTCs) have a role in predicting treatment efficacy of breast cancer. However, the relationship between CTC enumeration before neoadjuvant therapy and pathologic complete response rate is still uncertain. Methods: The study was exploratory. A total of 50 breast cancer patients were enrolled in a phase II clinical study of neoadjuvant therapy for HER-2-positive early breast cancer. They were enrolled for blood draws before and after neoadjuvant therapy. We used two methods (CellSearch and Tumor-Fisher) to detect CTCs. We compared the sensitivity of the two systems and investigated the correlation of the enumeration on baseline CTCs with the diagnosis, prognosis, and efficacy of neoadjuvant therapy of the patients with HER-2-positive early breast cancer. We also explored the dynamic change of CTCs after neoadjuvant therapy. Results: The sensitivity of Tumor-Fisher (27/50) method was significantly higher than that of the CellSearch system (15/50, p=0.008). The CTC numbers detected by the two detection systems were not significantly correlated with lymph node status, clinical stage, ki-67 level and hormone receptor status. Patients with ≥1 CTC before neoadjuvant therapy measured by the Tumor-Fisher system had a significant high pCR rate (74.1% vs. 39.1%, p = 0.013); whereas, there was no predictive effect on pCR by CellSearch system (73.3% vs. 51.4%, p = 0.15). Patients with a decrease in CTCs enumeration after neoadjuvant therapy were more likely to achieve pCR than those with no change or increase in CTCs enumeration (87.5% vs 50.0%, p = 0.015) by the Tumor-Fisher method. Unfortunately, there was no predictive value of CTCs enumeration for EFS before and after neoadjuvant therapy by two methods. Conclusions: Our study demonstrates that the new CTCs detection method Tumor-Fisher system has a higher checkout rate in early breast cancer than the CellSearch system, and shows the opportunity of CTC enumeration as a novel assistant biomarker to predict the response of neoadjuvant therapy in patients with HER-2-positive early breast cancer.